Modern treaty law and practice - Aust, Anthony (Cambridge ; New York : Cambridge University Press, 2007)
This text offers a treatment of the law of treaties written from the viewpoint of an experienced practitioner. Aust provides examples of the problems experienced with treaties on a daily basis, not just when the treaty is the subject of a courtcase.
Vienna convention on the law of treaties 1969 -- What is a treaty? -- MOUs -- Capacity to conclude treaties -- Full powers -- Adoption and authentication -- Consent to be bound -- Reservations -- Entry into force -- Treaties and domestic law -- Territorial application -- Successive treaties -- Interpretation -- Third states -- Amendment -- Duration and termination -- Invalidity -- The depositary -- Registration and publication -- Dispute settlement and remedies -- Succession to treaties -- International organisations -- Drafting and final clauses.
Includes bibliographical references and index.
Includes bibliographical references and index.
Keywords: Treaties; Traités.